Formação de professores indígenas : uma reflexão sobre a "Ação Saberes Indígenas na Escola" – rede UFMT/polo de Cuiabá - Silva, Leures Athaide da (2020)
This research discusses the process of training indigenous teachers in the “Action Indigenous Knowledge at School” Program (ASIE), offered by the extinct Secretariat for Continuing Education, Literacy, Diversity and Inclusion (SECADI), of the Ministry of Education (MEC), and coordinated by the Federal University of Mato Grosso (UFMT). ASIE / UFMT Network was organized in three centers: the Cuiabá Center, in partnership with the Federal Institute of Mato Grosso (IFMT), the Sinop Center, in partnership with the State University of Mato Grosso (UNEMAT), and the Barra do Garças Pole, in partnership with UFMT. In 2017, it served 11 indigenous peoples, out of 43 residents in the state of Mato Grosso. The analyzed documents were produced during the training that took place in Cuiabá, with teachers belonging to the Bororo, Chiquitano, Umutina, Nabikwara and Paresi peoples. The aim of the study is to understand the process of training indigenous teachers at the Cuiabá Center and to identify what literacy knowledge was learned by course participants, having as reference the post-constructivist didactics of the Education and Research Studies Group, Action and Research Methodology ( GEEMPA), expressed in the reports and, in particular, in the evaluations of teachers, in 2017. The studies carried out on the history of the ASIE Project / UFMT Network, and the initial training of teachers in Mato Grosso and the literature on indigenous school education in the Brazil guided the methodological choice of documentary analysis of the Project, based on the documents produced: school diagnoses, reports, and official documents, teacher evaluations after training and production of didactic materials from the GEEMPA training process. The history of indigenous school education is marked by the struggle of social movements and the achievement of specific rights for the indigenous peoples of Brazil. Studies on the organization of the UFMT Network show the relevance of higher education institutions and the partnerships of educators historically committed to the formation of indigenous teachers in Mato Grosso. The actions developed at the Cuiabá center explained the different methodological options for training in literacy, the main focus of the formation of the ASIE / MEC, carried out by the HEIs directly with the teachers and indigenous communities / villages involved. At the end of the research, it was possible to identify that the teachers developed significant knowledge about the processes of learning about literacy and the elaboration and production of didactic material within the specificity of each people regarding the linguistic characteristic and the own processes of learning about culture and culture. ethnic and cosmological identity that permeate this knowledge in each territory.